Perancangan Aplikasi Android Futsal Kita untuk Sistem Pemesanan Lapangan Menggunakan Metode RAD - Nanda Wahyudi Tanjung; Asrul Syabana; Muhammad Alda (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The digital era drives the need for convenience and efficiency in various aspects of life, including futsal field booking management. However, traditional futsal court booking processes are still mostly conducted manually, resulting in several issues such as unclear schedules, limited access to field availability information, inflexible rescheduling, and non-integrated payment systems. This study aims to describe the design and development of an Android application called Futsal Kita as an easy and efficient futsal field booking system using the Rapid Application Development (RAD) method. The RAD method is applied to support fast and iterative system development with active user involvement. The developed application provides real-time field availability information, online booking features, flexible scheduling options, secure and integrated payment systems, and digital invoices as transaction proof. The results of this study indicate that the Futsal Kita application improves booking efficiency and enhances user convenience in accessing futsal court services. Therefore, this application is expected to improve user experience and encourage the utilization of information technology in modern and integrated sports facility management.